(untitled) (Ágora de Heterodoxias, 2026)
Truth is a topic of great interest to humanity throughout history, varying in its definitions, nature, postulates, degree of social acceptance, essence, verifiability and other aspects. This review article aims to explore the paradigm of truth through a critical analysis of Augustinian philosophy and Lyotard’s metanarratives. The methodology employed for this article included documentary research, source review, and critical content analysis. The Augustinian conception of truth was presented, highlighting its nature, premises, means of access and qualities. Subsequently, the construct of metanarratives in modernism, according to Jean-François Lyotard was analyzed, highlighting its fragmented, subjective and consensus-based. A comparison was made between Augustine’s concept of truth and metanarratives, highlighting the convergences and divergences between the authors. The conclusions emphasize the existing variation in definitions of truth, the loss of a single, objective truth in favor of fragmented truths, epistemological confusion regarding truth, the loss of a universal order, and the rise of a relativism that leads humanity toward skepticism.